Mental Health Stigma in Diverse Cultures - Muhammad Younas ,; Amna Jabar,; Dr Ayesha Javed,; Tariq Rafique,; Maryam Khan,; Sadia Sohail, (Dialogue Social Science Review (DSSR), 2025)
The stigma of mental illness is a persistent challenge across the world and even more so in diverse cultures because the attitude toward mental illness could be different. This research examines the moderating effects culture plays on perceptions of mental health added stigma in different demographical populations. To understand whether there is any link between people’s cultural background and mental health stigma and in general to investigate the influence of cultural beliefs, demographics, and personal history on people’s attitudes to mental illness. A quantitative survey design using a cross-sectional was used to administer a questionnaire to 250 participants differing in their cultural, ethnic, and economic status. Participants responded to a demographic section of the questionnaire and 5-point Likert scale items assessing attitudes towards mental health, willingness to talk with others about the topic, and their propensity to seek therapy. The basic characteristics were presented using frequencies and percentages however for the data analysis more focused tests like chi-square tests and analysis of variance tests were used to determine the association between cultural factors and stigma. In assessing the internal consistency of the stigma scale, Cronbach’s alpha coefficient test was used. Mental health stigma also varied across cultural groups in the study. A significant number of respondents endorsed statements blaming mental health issues on weakness or instability wherever they held a collectivist frame of reference. The correlation between ease of speaking to people about mental health, and willingness to seek professional help was highly positive, pointing towards the need to continue the fight against the stigma surrounding mental health to increase the use of professionals. The Cronbach’s Alpha for the stigma scale was low (0.133), Current studies indicate that there is a variation in attitudes toward stigma across cultures, Therefore, the use of a single measure should be discouraged. There is a need alongside this study to encourage culturally specific interventions to reduce mental health stigma. Various measures should be employed to address stigma since different cultural beliefs and attitudes are bound to exist, especially in the modern society people living with mental disorders should come out and go for treatment. The results reemphasize the need to establish valid and culturally appropriate assessment instruments for capturing the concept of mental health stigma among culturally diverse groups.